A Designed 5‐Fluorouracil‐Based Bridged Silsesquioxane as an Autonomous Acid‐Triggered Drug‐Delivery System. Issue 38 (8th August 2013) - Giret, Simon; Théron, Christophe; Gallud, Audrey; Maynadier, Marie; Gary‐Bobo, Magali; Garcia, Marcel; Wong Chi Man, Michel; Carcel, Carole
Abstract Two new prodrugs, bearing two and three 5‐fluorouracil (5‐FU) units, respectively, have been synthesized and were shown to efficiently treat human breast cancer cells. In addition to 5‐FU, they were intended to form complexes through H‐bonds to an organo‐bridged silane prior to hydrolysis‐condensation through sol–gel processes to construct acid‐responsive bridged silsesquioxanes (BS). Whereas 5‐FU itself and the prodrug bearing two 5‐FU units completely leached out from the corresponding materials, the prodrug bearing three 5‐FU units was successfully maintained in the resulting BS. Solid‐state NMR (29Si and 13C) spectroscopy show that the organic fragments of the organo‐bridged silane are retained in the hybrid through covalent bonding and the 1H NMR spectroscopic analysis provides evidence for the hydrogen‐bonding interactions between the prodrug bearing three 5‐FU units and the triazine‐based hybrid matrix. The complex in the BS is not affected under neutral medium and operates under acidic conditions even under pH as high as 5 to deliver the drug as demonstrated by HPLC analysis and confirmed by FTIR and 13C NMR spectroscopic studies. Such functional BS are promising materials as carriers to avoid the side effects of the anticancer drug 5‐FU thanks to a controlled and targeted drug delivery.